Stridhana and Hindu Women’s Property Rights in Bangladesh: A Legal Analysis of the Dayabhaga Tradition (Dhaka University Law Journal, 2025)
This article explores the concept of stridhana within the Dayabhaga school of Hindu law for its historical, legal, and contemporary relevance in relation to the property rights of Hindu women in Bangladesh. It traces the evolution of stridhana from the Vedic to Smriti periods, highlighting its recognition as women’s exclusive property through Jimutavahana’s Dayabhaga. The article further examines the classification, acquisition, and control of stridhana, contrasting Dayabhaga’s liberal approach with the more restrictive Mitakshara school. It further touches on some contemporary issues facing Hindu women in Bangladesh: patriarchal control, inconsistencies in the judiciary, and a lack of codified law. The article looks at court decisions and reform proposals and calls for a codified Hindu personal law and a gender-sensitive judicial approach. It contributes to the discourse on Hindu women’s property rights in Bangladesh offering a pathway in which the law can be reformed to bring greater gender equality.Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 63-88